Effect of an Inquiry-Based Blended Learning Module on Electronics Technology Students’ Academic Achievement - Mohammad Hussain, Mohd Azlan; Ahmat Zainuri, Nuryazmin; Mohd Zulkifli, Rafeizah; Abdul Rahman, Anesman (Journal of Technical Education and Training, 2023)
Technological advances have led to a change in teaching strategies applied in Technical and Vocational settings. An effective teaching strategy is needed to address issues encountered in the traditional learning process of Electronics Technology Students at Malaysian Vocational College. Blended learning is one of the best teaching strategies for Electronic Technology courses as it is in line with the 21st-century learning, especially in promoting student-centred and life-long learning. This study looks at the impact of an Inquiry-Based Blended Learning (IBBL) module on the students’ achievement in the Industrial Electronics Equipment Problem Solving (IEEPS) Course, in an Electronic Technology Program. This study uses an experimental study design through the quasi-experimental method to evaluate the effectiveness of the module. The comparison of achievement between an experimental group and a control group was conducted based on the pre-test and post-test protocol. The findings of the evaluation phase through the t-test showed that there was a significant difference (p<.05) between the experimental group and the control group. This indicated that using an Inquiry-Based Blended Learning Module was effective to help the student to improve their achievement in Industrial Electronics Equipment Problem Solving Course. Therefore, the inquiry-based blended learning module has the potential to be applied by instructors and students in the Vocational College setting.